Analisis penerapan UU Nomor 1 Tahun 2022 tentang HKPD dalam tata cara pemungutan pajak barang dan jasa tertentu serta kontribusinya pada Pendapatan Asli Daerah - Kalangi, Karenina Noviany; Pangerapan, Sonny; Suwetja, I Gede (Riset Akuntansi dan Portofolio Investasi, 2025)
This study examines the implementation of Law No. 1 of 2022 concerning Financial Relations Between the Central and Regional Governments in the collection of Specific Goods and Services Tax (PBJT) in Manado City and its contribution to Regional Original Revenue (PAD). The research employed a qualitative approach supported by interviews, documentation, and analysis of primary and secondary data. Findings indicate that the PBJT collection process in Manado has generally followed the provisions of Law No. 1 of 2022, although the Mayor’s implementing regulation has not yet been enacted, and entertainment service tariffs remain inconsistent. In 2022–2023, PBJT contributed 66.05% and 65.81% to PAD respectively, dominated by restaurant tax (around 30%) and street lighting tax (around 20%), while entertainment and parking taxes contributed less than 5%. In 2024, following the enactment of the new law, PBJT’s contribution was recorded at 64.35%, still primarily from food and beverage services. The study concludes that while PBJT plays a significant role in supporting PAD, improvements are needed in regulatory enforcement, taxpayer compliance, and digital-based collection systems.